SMALL MOLECULE ACCURATE RECOGNITION TECHNOLOGY(SMART) TO ENHANCE NATURAL PRODUCTS RESEARCH (International Journal of Food and Nutritional Sciences, 2021)
Various algorithms comparing 2D NMR spectra have been explored for their ability todereplicate natural products as well as determine molecular structures. However,spectroscopic artefacts, solvent effects, and the interactive effect of functional group(s) onchemical shifts combine to hinder their effectiveness.